Visualised AKIS Diagnosis – an Instrumental Approach to Support AKIS Appraisal - Andrea Knierim; Fanos M. Birke (EuroChoices, 2023)
The AKIS (Agricultural Knowledge and Innovation System) concept is now widely applied in the EU partly due to latest CAP regulation. Visualisation-based AKIS diagnosis relies on the iterative elaboration of an AKIS diagram that provides a static picture of what elements of the system are linked through what kind of relations in which socio-economic contexts and environments. In this article we discuss the implications of using the visualised AKIS diagnosis method based on our empirical assessment of AKIS in 28 European countries. The method involved drafting AKIS diagrams based on targeted desk research, conducting dialogues with experts affiliated with or overseeing prominent knowledge organisations to adjust and refine the diagrams and to analyse actor diversity and linkages. The final diagrams and the background reports on AKIS appraisal were used to deepen the AKIS understanding among various stakeholders in the agriculture sector, as well as an input for the CAP strategic plan preparation in some countries. We conclude that the visualised AKIS diagnosis has a great potential to make complex knowledge infrastructures and exchange processes tangible. However, it also comes with risks, for example, that the snapshot in time may become misleading, through being an outdated or erroneous representation.
Keywords: 630